SINGLE–PARENT FAMILIES–SOCIAL STATUS, NEEDS AND CHALLENGES - Anita Burgund; Marina Pantelic; Marko Milanovic (Human Research in Rehabilitation, 2013)
There is no doubt that pluralization of society and societal conditions have an impact on the modern family, its role and structure. Changes in the hierarchy of societal values and attitude of society towards family lead to significant changes in its structure and way of functioning. The image of the family consisting of father, mother and children has more often been replaced by the image of families with one parent and children. There are multiple causes of single-parent families (single parenthood) such as death, divorce, abandonment of the family by one of the parents, etc. The positions and attitude of society towards single-parent families is different and it’s actually depending on the cause of their occurrence. The aim of this paper was to identify basic needs and challenges of single-parent families in Serbia. For this purpose, we have organized three focus groups with 18 single mothers (six in each focus group). The results are presented in the context of creating new policies for improving the position of single-parent families in Serbia.